2018
DOI: 10.1007/978-3-319-91602-6_16
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Large-Scale Agile Development with Domain-Driven Design

Abstract: Abstract. An increasing number of large organizations are adopting agile and lean methods at larger scale for building complex software systems. One major critique of agile development and in particular of large-scale agile development is the neglect of proper architecting assistance in such development efforts. On the one hand, emergent architecture design may require excessive redesign efforts in large systems, while on the other hand, big upfront architecture delays the starting point of implementation. Dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 14 publications
(30 reference statements)
0
16
0
Order By: Relevance
“…[7], [20]) or they study the overall methods in a collective, aggregated manner that does not allow researchers or practitioners to compare and contrast these methods (e.g. [6], [8], [9], [18], [21], [22], [23]). This study is also the first to include custom-built methods (RQ1).…”
Section: Contributions Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…[7], [20]) or they study the overall methods in a collective, aggregated manner that does not allow researchers or practitioners to compare and contrast these methods (e.g. [6], [8], [9], [18], [21], [22], [23]). This study is also the first to include custom-built methods (RQ1).…”
Section: Contributions Of the Studymentioning
confidence: 99%
“…After removing duplicates, the titles and abstracts of the remaining articles were read. We identified 19 relevant systematic literature reviews in this area ( [4], [6], [7], [9], [17], [20], [21], [22], [23], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42]). By reading the titles of articles that cite these reviews, we identified three more relevant articles ( [18], [43], [44]).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors often result in coordination challenges and additional coordination efforts [9,27]. For instance, an overarching figure or role, as well as appropriate methods, are required to coordinate the teams and address team-crossing challenges [11]. However, inter-team coordination in software ecosystems rises additional complications as the teams are distributed over several organizations who rarely share common goals or strategies nor a centralized control figure who coordinates them.…”
Section: Related Workmentioning
confidence: 99%
“…The application of scaled agile methods has already been investigated to a great extent, e.g. in [3,[6][7][8][9][10], and [11]. The focus, however, lies mostly on large-scale projects or multiteams within one organization.…”
Section: Introductionmentioning
confidence: 99%